Leading under pressure: evaluating the decision-making style of NHL coaches. Issue 1 (13th March 2017) - Trottier, Kim
Abstract : Purpose: The purpose of this paper is to establish the optimal decision-making style in a fast-paced, complex, and dynamic environment. Design/methodology/approach: Three decision-making attributes are explored: the use of intuition vs analysis, the proclivity to heuristics, and susceptibility to bias. The intuition/analysis is tested with a questionnaire that has been validated in prior research, while information on the two other dimensions is from an exploratory survey designed for this purpose. Responses to the survey questions provide some insight into the differential decision-making style of elite NHL hockey coaches' vis-à-vis amateur coaches and news reporters. Findings: The data suggest elite decision makers have no preference for intuitive or analytical settings, but exhibit a significantly higher perception of their ability to perform in both. While current literature shows sports athletes to be more intuitive, it appears coaches excel on the analytical dimension instead. This study finds that while elite hockey coaches have fewer biases overall, they tend in particular to be overly optimistic in comparison to amateur coaches and news reporters. Research limitations/implications: The main limitation in this paper is that the survey on heuristics and biases is exploratory, making these results less robust than the findings on intuition and analysis. Originality/value: This paper is first to extend the decision-making literature to coaches, and among few papers that obtain insights from NHL coaches directly. The findings are likely to extend to corporate leadership as well, increasing the relevance of the results.